Analisis Modal dan Modifikasi Struktur Pompa Closed Drain 510-P9002 untuk Mitigasi Getaran di Lapangan Jambaran Tiung Biru - Achmad Walid; Irwanda Yuni Pungkiarto; Mohammad Rizanto Juliarsyah; Khoirul Anwar (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study presents a modal analysis of Pertamina EP Cepu’s closed drain pump 510-P9002, which operates in the condensate–water treatment unit of the Jambaran Tiung Biru field. Field vibration measurements conducted in August 2024 indicated a fundamental frequency of 25 Hz, corresponding to 1×RPM of the driving motor, with maximum amplitudes reaching 13.46 mm/s. Such excessive vibration poses risks of mechanical damage, reduced equipment service life, and potential operational failure. To address this issue, finite element analysis (FEA) was employed to examine the dynamic response of the pump, determine its natural frequencies, and identify possible resonance conditions. A CAD model of the pump–vessel assembly was developed, meshed, and analyzed under actual boundary conditions. The results showed several natural frequencies ranging between 23.16 and 26.65 Hz, which are close to the excitation frequency, suggesting a very high likelihood of resonance. Various structural modifications were then evaluated, including a half casing and two types of full casings. Among these, the full casing B design provided additional stiffness in the motor support area; however, none of the modifications effectively reduced vibration within the internal components. Based on these findings, the study recommends the implementation of a dynamic vibration absorber (DVA) tuned to the excitation frequency, along with the redesign of structural components to shift natural frequencies away from operating excitation. These solutions are expected to improve operational stability, extend equipment lifespan, and enhance overall system reliability. The outcomes of this research provide important insights for managing vibration issues in pump systems operating under similar conditions, particularly in the oil and gas industry where continuous, stable operation is critical.